Informed Choices on Marriage, Childlessness and Reproductive Technologies : An African Christian Theological and Ethical Reflection - Ganusah, Rebecca (Ghana bulletin of theology, 2008)
It is not an overstatement to say that a great value is placed on fertility or childbirth in Africa. Couples who have married for say three years without a child, therefore, face moments of anxiety, as people begin to wonder whether there is not something going wrong somewhere. The problem of infertility becomes even more heightened in the African context, where some see marriage as being "incomplete without children". Can an African couple enjoy their marriage even without children? In this presentation, we want to reflect on the concepts as held in Africa about marriage, childlessness and some reproductive technologies that are used to help in overcoming childlessness in marriage. The reflection is intended to help in making informed choices.